HYBRID ALGORTHIM IN OBJECT CACHE SYSTEMS - AL-ZGOOL MOSAB BASSAM (Advanced Engineering Research)
In this paper the hybrid algorithms in object caching system is considered. The method using hybrid algorithm in implementation of the adaptive caching systems is offered. The new universal method hybridization of two and more caching algorithms is described. The description of the new hybrid (of the algorithm LRU and LFU) algorithm, namely Random Recently/Frequently Used (RRFU) is presented. The result of comparative study of the new algorithm RRFU and well-known hybrid algorithm LRFU is showed.